Seroprevalence to the antigens of Taenia solium cysticercosis among residents of three villages in Burkina Faso: a cross-sectional study. - Hélène Carabin; Athanase Millogo; Nicolas Praet; Sennen Hounton; Zékiba Tarnagda; Rasmané Ganaba; Pierre Dorny; Pascal Nitiéma; Linda D Cowan; Evaluation du Fardeau Economique de la Cysticercose Au Burkina Faso (EFECAB) (Public Library of Science (PLoS), 2009)
There is limited published information on the prevalence of human cysticercosis in West Africa. The aim of this pilot study was to estimate the prevalence of Taenia solium cysticercosis antigens in residents of three villages in Burkina Faso.Three villages were selected: The village of Batondo, selected to represent villages where pigs are allowed to roam freely; the village of Pabré, selected to represent villages where pigs are usually confined; and the village of Nyonyogo, selected because of a high proportion of Muslims and limited pig farming. Clustered random sampling was used to select the participants. All participants were asked to answer an interview questionnaire on socio-demographic characteristics and to provide a blood sample. The sera were analysed using an AgELISA. The prevalence of "strong" seropositive results to the presence of antigens of the larval stages of T. solium was estimated as 10.3% (95%CI: 7.1%-14.3%), 1.4% (0.4%-3.5%) and 0.0% (0.0%-2.1%) in the 763 participants who provided a blood sample in Batondo, Pabré and Nyonyogo, respectively. The prevalence of "weak" seropositive test results to the presence of antigens of the larval stages of T. solium was 1.3% (0.3%-3.2%), 0.3% (0.0%-1.9%) and 4.5% (2.0%-8.8%) in Batondo, Pabré and Nyonyogo, respectively. The multivariate logistic regression, which included only Batondo and Pabré, showed that village, gender, and pork consumption history were associated with AgELISA seroprevalence.This study illustrates two major points: 1) there can be large variation in the prevalence of human seropositivity to the presence of the larval stages of T. solium cysticercosis among rural areas of the same country, and 2) the serological level of the antigen, not just whether it is positive or negative, must be considered when assessing prevalence of human cysticercosis antigens.